Faseverbernes tidsbetingelse. Grundtræk af den semantiske beskrivelse af faseverbkonstruktioner - Volkmar Engerer (Hermes, 2002)
In this paper I argue for a special “aspectual condition” that constitutes the class of phase verbs like begin, continue and stop in Danish and German. It is shown that phase verbs demand a minimum of time structure on the part of their syntactic complements (durative, telic etc.). Their meaning is modelled by a function that maps the truth intervals of their complements into part intervals, on which the truth of the complete sentence is evaluated. This operator approach to the semantics of phase verbs is explicated in a Montague-like design where the ingressive, continuative and egressive operators have scope over complement-derived propositions and produce as output new truth conditions that now evaluate propositions at the start, middle and end interval respectively. This solution to semantics of phase verbs covers, as I argue, a central aspect of their meaning, but leaves other problems unsolved, like, for example, ambiguity phenomena that cannot be modelled satisfactorily in Montague-like semantics. This point is demonstrated with continuative phase verbs that seem to present particular problems.